Pengaruh berbagai jenis bahan amandemen tahan terhadap beberapa sifat kimia gambut - Nazli, Khairul; Nurhayati, Nurhayati; Zuraida, Zuraida (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala)
This study was aimed at determining kinds of soil amendements that increase fertility on peat soil.Â The research was conducted in Soil Chemistry Laboratory, Agriculture Faculty, Syiah Kuala University, Darussalam Banda Aceh from December 2013 to March 2014.Â The experiment was arranged in a completely randomized design (CRD) with 8 treatments and three replications. Kinds of soil amandements evaluated were: control, mineral soil, sawdust, lime, mineral soil + sawdust, mineral soil + lime, sawdust + lime, sawdust + lime+ mineral soil.Â The result showed that the amendements increased pH(H2O), P-available, base saturation and decreased Cation Exchange Capacity (CEC). Sawdust + lime had the highest ability to increased P-avaiable. Lime had the highest ability to increased base saturation. Sawdust + mineral soil had the highest ability to decreased CEC.